Academic Senate Minutes 2010-04-15 - Academic Senate:::::::::
Chair Report. Agenda amended and approved. Minutes delayed. Global Studies revision to major and concentrations approved. President Report. Provost Report. Special Report: Interim Mayor of Cotati – R. Coleman-Senghor. New Section 6 of Article V of by-laws recommendation approved. Creation of a Senate Diversity Subcommittee approved. Revision to the Periodic Evaluation of Temporary Faculty approved. Vice President of SAEM Report. CFA Report. Resolution to hold a Referendum of No Confidence in the Financial Management of Sonoma State University and a Call for the Resignation of President Ruben Armiñana and CFO/VP for Administration and Finance, Larry Furukawa-Schlereth – First Reading. Vice President of Administration and Finance Report. Arts and Humanities GE Reform proposal approved. Good of the Order.